Myth and reality : the struggle for freedom in India, 1945-47 - Gupta, Amit Kumar, 1936- (New Delhi : Manohar, 1987)
Papers presented at a symposium organized by the Nehru Memorial Museum and Library, New Delhi, Feb. 13-17, 1984.
Includes bibliographies and index.
Keywords: India -- Politics and government -- 1919-1947 -- Congresses